2016
DOI: 10.1002/art.39792
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Signatures of Salivary Gland Inflammation in Sjögren's Syndrome

Abstract: ObjectiveSjögren's syndrome (SS) is a complex multisystem autoimmune disease that results in progressive destruction of the exocrine glands. The purpose of this study was to characterize epigenetic changes in affected gland tissue and describe the relationship of these changes to known inflammatory processes.MethodsA genome‐wide DNA methylation study was performed on human labial salivary gland (LSG) biopsy samples obtained from 28 female members of the Sjögren's International Collaborative Clinical Alliance (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 45 publications
4
44
1
Order By: Relevance
“…With this in mind, quantitative analysis of 485 577 CpG sites in pSS peripheral blood naïve CD4 + T cells and CD19 + B cells was conducted using the Illumina HumanMethylation (HM) 450 K array, leading to the characterisation of new pathways 2–4. In contrast, the EWAS study performed in minor salivary glands (MSG) showed modest variations in DNA methylation,2 5 while we have recently observed global DNA methylation alterations in salivary gland epithelial cells (SGEC) from patients with pSS leading to, among other perturbations, sicca syndrome (SS) B/La autoantigen deregulation 6 7. As the cellular heterogeneity in the MSG biopsies may explain this paradox, long-term cultured SGEC were selected to conduct an EWAS study.…”
Section: Introductionmentioning
confidence: 94%
“…With this in mind, quantitative analysis of 485 577 CpG sites in pSS peripheral blood naïve CD4 + T cells and CD19 + B cells was conducted using the Illumina HumanMethylation (HM) 450 K array, leading to the characterisation of new pathways 2–4. In contrast, the EWAS study performed in minor salivary glands (MSG) showed modest variations in DNA methylation,2 5 while we have recently observed global DNA methylation alterations in salivary gland epithelial cells (SGEC) from patients with pSS leading to, among other perturbations, sicca syndrome (SS) B/La autoantigen deregulation 6 7. As the cellular heterogeneity in the MSG biopsies may explain this paradox, long-term cultured SGEC were selected to conduct an EWAS study.…”
Section: Introductionmentioning
confidence: 94%
“…63 It was shown that global DNA hypomethilation is typical of inflamed cells and that the epigenetic status of the inflammatory genes represents the major contributor to DNA methylation differences. 64 Recently, we showed that proinflammatory actions of IL-1β in differentiated Caco-2 cells also involve epigenetic mechanisms. In particular, IL-1β is able to change the methylation status acting as demethylating agent.…”
Section: Dna Demethylationmentioning
confidence: 99%
“…Recent studies have reported epigenetic alterations such as changes in DNA methylation, histone modification, micro-RNA expression, and have found defective DNA methylation to be associated with SSB gene expression and lymphocyte infiltration in pSS [7577]. Just recently, a genome-wide DNA methylation study on human labial salivary glands of SS was presented [78]. Several genes and pathways previously thought to be involved in disease-related processes as well as a number of new candidates were discovered.…”
Section: Pathogenesismentioning
confidence: 99%
“…Several genes and pathways previously thought to be involved in disease-related processes as well as a number of new candidates were discovered. Interestingly, a correlation was recognized between DNA methylation and a set of genes previously found highly differentially expressed in pSS and healthy salivary glands [59, 78]. Furthermore, genome-wide DNA methylation profiles showed prominent hypomethylation of interferon-regulated genes in whole blood and CD19+ cells in pSS [79•].…”
Section: Pathogenesismentioning
confidence: 99%